Current status of real-world big data research in the cardiovascular field in Japan. Issue 3 (March 2023) - Tonegawa-Kuji, Reina; Kanaoka, Koshiro; Iwanaga, Yoshitaka
Summary: Real-world data (RWD) are observational data obtained by collecting, structuring, and accumulating patient information among the medical big data. RWD are derived from a variety of patient medical care and health information outside of conventional research data, and include electronic health records, claims data, registry data of disease, drug and device, health check-up data, and more recently, patient information data from wearable devices. They are currently being utilized in various forms for optimal medical care and real-world evidence (RWE) is constructed through a process of hypothesis generation and verification based on the RWD research. Together with classic clinical research and pragmatic trials, RWE shapes the learning healthcare system and contributes to the improvement of medical care. In the cardiovascular medical care of the current super-aged society, the need for a variety of RWE and the research is increasing, since the guidelines established over time and the medical care based on it cannot necessarily be the best in accordance with the current medical situation. In this review, we focus on the RWD and RWE studies in the cardiovascular medical field and outlines their current status in Japan. Furthermore, we discuss the potential for extending the studies and issues related to the use of medical big data and RWD. Graphical abstract: Unlabelled Image Highlights: Real-world data include electronic health records, claims, and health check-up data. Real-world evidence is established through real-world big data research. They contribute to medical care improvement through learning healthcare system. A variety of cardiovascular research using the real-world big data are in progress. Further/continuous efforts are required to construct/leverage real-world big data.